2018
DOI: 10.1111/jgh.14317
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal: Olmesartan‐induced enteropathy

Abstract: A 69-year-old woman presented with a 5-week history of profuse, watery diarrhea. The past medical history was of hypertension treated with olmesartan 40-mg Po daily for 8 years. Initial investigations revealed an elevated serum creatinine at 117 μmol/L (50-100 μmol/L) and C-reactive protein of 11 (0-8 mg/L).She was admitted with a presumptive diagnosis of viral gastroenteritis and acute kidney injury, and intravenous hydration was commenced, and olmesartan withheld, with normalization of serum creatinine. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 0 publications
3
12
0
1
Order By: Relevance
“…Clinical improvement typically occurs within days to a week [13,15,17] after olmesartan is suspended, as was seen with our case. Repeat EGD with biopsies 4 months after our patient's hospitalization confirmed histologic resolution of her enteropathy.…”
Section: Basharisupporting
confidence: 73%
See 1 more Smart Citation
“…Clinical improvement typically occurs within days to a week [13,15,17] after olmesartan is suspended, as was seen with our case. Repeat EGD with biopsies 4 months after our patient's hospitalization confirmed histologic resolution of her enteropathy.…”
Section: Basharisupporting
confidence: 73%
“…Additionally, a crucial factor to consider that has occurred in previous cases [ 1 , 6 , 7 , 10 , 11 , 13 - 15 ] but not particularly emphasized is how hospitalized patients frequently have their home olmesartan medication temporarily suspended prior to a formal diagnosis. Reasons for this include therapeutic interchange to an alternate ARB due to the institutional formulary, held for medical reasons such as hypotension or acute kidney injury, or held along with all other drugs for suspicion of a possible drug-induced phenomenon of unknown etiology.…”
Section: Discussionmentioning
confidence: 99%
“…However, neither DQ2 nor DQ8 was present in our patient's case. Previous reports have shown that improvement of symptoms begins in approximately 1 week [5,6], and that the average time to complete improvement of symptoms is 8 months [2]. Our patient's symptoms improved in approximately 3 months, with no results contradictory to the past reports.…”
Section: Discussionsupporting
confidence: 48%
“…Alzueta et al demonstrated a case of Telmisartan associated enteropathy with cessation following drug withdrawal 6 . DeBortoli at al in 2017 conducted a large based population study on patients treated with ARB therapy in Italy and Germany which associated ARB‐induced SLE but with a relatively low incidence 2,7 . Hence, it can be postulated that this is most likely a class effect.…”
Section: Discussionmentioning
confidence: 99%